(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the role of sociology in the system of social sciences and its interrelated aspects with other sciences. The role of the science of sociology in the development of society as a whole system and its importance and peculiarities in social relations are analyzed. Sociology is a science that studies the laws of occurrence of social units, organizations, processes and relations. Sociology has methods of data collection and analysis, analysis and conclusions in the system of other social sciences.